STUDY ON AUTOMATION PROGRAMMING TO MONITOR AND CONTROL A SCREW ELECTRO-COMPRESSOR (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
The article describes the programming architecture of a programmable logic controller (PLC) and an operator panel that is part of an automation cabinet of a screw electro-compressor. Behind the operation of a screw electro-compressor, there is a programming logic presented in the article that is implemented according to the requirements of each project. The article presents all the states of a screw compressor that are implemented in the PLC by a programmer in the form of software sequences. The article depicts the logic diagrams used to facilitate the software implementation process. Following the software implementation in the PLC of the logic diagrams, the article has a second software that contains a series of screens for the operator panel. The operator panel is a touch-screen type and communicates with the PLC through a defined communication protocol displaying the parameter values in real time on the programmed screens. The software developed for the operator panel by a programmer has the role of facilitating a human operator to monitor parameters and transmit commands to the screw electro-compressor. The article ends by presenting the conclusions that argue the efficiency and safety in operation through the presented software concept of a screw electro-compressor.
Keywords: Programming; Programmable logic controller (PLC); Operator panel; Automation cabinet; Screw electro-compressor; Logic diagram; Software state; Screen